The Frequency of Nasal Septal Abscess and Its Related Factors in Patients Referred to a Hospital in North of Iran - Sevil Nasirmohtaram; Maryam Akbari; Maliheh Akbarpour; Farnaz Mazloom (مجله دانشگاه علوم پزشکی گیلان)
Background Nasal septal abscess, which is the collection of purulent materials between the cartilaginous or bony septum and the mucoperichondrium or mucoperiosteum, often occurs after septal hematoma caused by trauma. Other common factors include surgery, foreign bodies, and sinusitis. In addition to the risk of nasal deformity, septal abscess can cause life-threatening complications such as osteomyelitis, orbital or intracerebral abscess. Objective This study aims to investigate the frequency of nasal septal abscess and its related factors in patients in north of Iran. Methods In this descriptive cross-sectional study on the patients referred to a hospital in north of Iran in 2022. Their demographic and disease-related information were recorded and the risk factors were finally identified. Results In this study, 37 patients had septal abscess. The most common risk factor identified was a history of septoplasty or septorhinoplasty (35.1%), followed by diabetes mellitus (21.6%). Surprisingly, one of the factors in these patients was cauterization for epistaxis treatment (n=6). All patients were treated with broad-spectrum antibiotics and surgical drainage. In five patients, abscess resulted in saddle nose deformity. Positive culture results were reported in five samples. Conclusion Early identification of nasal septal abscess and its risk factors can help control the disease and prevent its serious complications.